Global climate change and crop resistance to aphids: contrasting responses of lucerne genotypes to elevated atmospheric carbon dioxide - Johnson, S.N; Ryalls, J.M.W; Karley, A.J (Annals of applied biology, 2014)
Predicted increases in atmospheric carbon dioxide (CO₂) concentrations could modify crop resistance to insect herbivores by altering plant quality. The short generation times of aphids may allow them to exploit such changes and colonise previously resistant plant genotypes. Lucerne (Medicago sativa) has undergone global selective breeding against aphids, including the pea aphid, Acyrthosiphon pisum. The purpose of this study was to characterise how ambient CO₂ (aCO₂) and elevated (eCO₂) (400 and 600 µmol mol⁻¹, respectively) affected plant physiological traits potentially linked to aphid resistance, focussing on foliar amino acid concentrations, across five M. sativa genotypes with varying resistance to A. pisum. These included susceptible (Hunter River), low (Trifecta), moderate (Aurora and Genesis) and high resistance (Sequel). Under eCO₂, root nodulation doubled and essential amino acid concentrations increased by 86% in resistant Sequel, whereas essential amino acid concentrations decreased by 53% in Genesis. Moreover, concentrations of lysine, an amino acid whose deficiency has been linked previously to A. pisum resistance in M. sativa, increased by 127% in Sequel at eCO₂. Compared with aCO₂, aphid colonisation of Sequel plants rose from 22% to 78% and reproduction rates increased from 1.1 to 4.3 nymphs week⁻¹ under eCO₂ conditions. In contrast, Genesis became more resistant at eCO₂ compared with plants at aCO₂; aphid colonisation rates fell from 78% to 44% of plants and reproductive rates decreased from 4.9 to 1.7 nymphs week⁻¹. In conclusion, predicted changes in atmospheric CO₂ concentrations could either reduce (Sequel) or enhance (Genesis) resistance to aphids, which might be linked to quantitative and qualitative changes in foliar amino acids.